Early flora colonization affects intestinal immunoglobulin G uptake in piglets, which may be mediated by NF-κB-FcRn pathway - Peng, Fang; Zhang, Haihan; He, Xi; Song, Zehe (Frontiers in Microbiology, 2023)
The passive immunity of newborn piglets is mainly derived from immunoglobulin G (IgG) in breast milk, and the incomplete transfer of passive immune is considered to be an important cause of piglet death. This study was conducted to investigate the effect of early intestinal flora colonization on IgG uptake and its possible mechanism. The newborn piglets and IPEC-J2 cells were used to investigate the possible factors and regulatory mechanisms affecting intestinal IgG uptake. In vivo, 40 piglets were euthanized postnatal on d 0, 1, 3, or 7, with 10 piglets per time. The blood sample, gastric contents, jejunal contents and mucosa were collected for analysis. In vitro, IPEC-J2 cells transwell culture system was used to establish the IgG transporter model to explore the specific regulatory mechanism of IgG transport. Our results demonstrated that the intestinal IgG uptake was positively correlated with the expression of Neonatal Fc receptor (FcRn). With the increase of age, the intestinal flora of newborn piglets was gradually enriched. The function of intestinal genes also changes with the colonization of intestinal flora. We found that the expression trend of TLR2, TLR4 and NF-κB (P65) in intestine was consistent with that of FcRn. Furthermore, the in-vitro results demonstrate that the NF-κB signaling pathway is involved in regulating FcRn-mediated IgG transmembrane transport. In conclusion, early flora colonization affects intestinal IgG uptake in piglets, which may be mediated by NF-κB-FcRn pathway.